The encounter (Canadian Medical Education Journal, 2019)
We know that homelessness is a nation-wide problem in Canada. What may be often forgotten, especially by those of us unfamiliar with poverty and deprivation, is how homelessness affects a person’s health. In this essay, I narrate a chance encounter with a homeless man that taught me the difficulties homeless people face in accessing, navigating, and benefiting from the health care system. We need to rethink how we health care providers respond to the homeless, and medical students can help lead the change.